Paddling technique for 200 m sprint kayak - Nikonorov, A. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
Sprint paddling technique should be the most efficient motion to achieve a racing target. The concept of the efficient paddling technique has been fairly well established over a few last Olympic cycles. However with the introduction of the 200m racing distance the notion of efficiency of canoeing technique must be fundamentally changed. Efficient 1000m technique should help to sustain racing speed during the race. Maximum speed doesn't play a relevant role for this race. Many athletes are able to achieve peak 1000m racing speed paddling at shorter distance, but this doesn't guarantee good eventual performance. Performance over 200m is significantly limited by peak speed capacity over the first part of the race. The second part of the race is limited by the athlete's endurance and efficiency of the technique in a way similar as in a 1000m race. So, the targets of teaching paddling technique for 200m and 1000m racing should be different. Teaching for 1000m aims predominantly to improve the bio-energetic efficiency of the motion, but teaching for 200m needs find ways to bring maximum speed to the top level as well as improving the efficiency. Before outlining the strategy of technical preparation for 200m racing we have to describe and understand the following crucial notions: